Known pathogenic gene variants and new candidates detected in Sudden Unexpected Infant Death using Whole Genome Sequencing - Bard, Angela M; Clark, Lindsay V; Cosgun, Erdal; Aldinger, Kimberly A; Timms, Andrew; Quina, Lely A; Lavista Ferres, Juan M.; Jardine, David; Haas, Elisabeth A; Becker, Tatiana M; Pagan, Chelsea M; Santani, Avni; et al. (American Journal of Medical Genetics, 2024)
The purpose of this study is to gain insights into potential genetic factors contributing to the infant's vulnerability to Sudden Unexpected Infant Death (SUID). Whole Genome Sequencing (WGS) was performed on 144 infants that succumbed to SUID, and 573 healthy adults. Variants were filtered by gnomAD allele frequencies and predictions of functional consequences. Variants of interest were identified in 88 genes, in 64.6% of our cohort. Seventy-three of these have been previously associated with SIDS/SUID/SUDP. Forty-three can be characterized as cardiac genes and are related to cardiomyopathies, arrhythmias, and other conditions. Variants in 22 genes were associated with neurologic functions. Variants were also found in 13 genes reported to be pathogenic for various systemic disorders and in two genes associated with immunological function. Variants in eight genes are implicated in the response to hypoxia and the regulation of reactive oxygen species (ROS) and have not been previously described in SIDS/SUID/SUDP. Seventy-two infants met the triple risk hypothesis criteria. Our study confirms and further expands the list of genetic variants associated with SUID. The abundance of genes associated with heart disease and the discovery of variants associated with the redox metabolism have important mechanistic implications for the pathophysiology of SUID.